ANALYSIS OF THE RELATIONSHIP BETWEEN PESTICIDE USE AND HEALTH COMPLAINTS IN RICE FARMERS IN GAMPONG BAK PAOH LAMNO, ACEH JAYA REGENCY - Alkhair, M. Hafizh; Zakaria, Radhiah; Ariscasari, Putri (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: Improper use of pesticides can lead to health complaints among farmers due to direct exposure, both acute and chronic. Method: This study employed a cross-sectional design with a sample of 78 rice farmers in Gampong Bak Paoh Lamno, selected from a total of 350 pesticide users. Data were collected through interviews using questionnaires and analyzed using the Chi-Square test with SPSS. Result: A total of 75.6% of respondents reported health complaints. Variables significantly associated with health complaints included pesticide use practices (p value = 0.000), knowledge (p value = 0.000), attitude (p value=0.001), duration of exposure (p value = 0.000), and age (p value = 0.000). Cholinesterase tests on two selected respondents showed levels below the normal range, indicating pesticide exposure. Recommendation: For the safety of farmers, it is expected that the relevant parties will be able to conduct cholinesterase tests on all pesticide users, and it is necessary to hold a routine training programme to improve understanding the correct pesticide use procedures.